Advances in experimental studies of internal motions of non-linear macromolecular systems in solutions. (22nd June 2022) - Zhu, Mo; Ishaq, Muhammad Waqas; Li, Lianwei
Abstract: The internal motions of macromolecular systems in solutions are closely related with the microscopic relaxation and macroscopic rheological behavior, therefore, this topic has been extensively studied both theoretically and experimentally. It is well-known that for a flexible or semi-flexible macromolecules with sufficient large chain size, there are two basic modes of motions in dilute solution, namely, translational motion of center of mass of a chain, and internal motions of segments with respect to the center of mass of a chain. In the past few decades, the advancement in characterization and analysis methods make it possible to distinguish both modes of motions experimentally. Although a significant experimental progress has been achieved to understand the intrachain dynamics and test the predictions by classical theory, previously published reviews have been only focused on the linear chain system with the simplest architecture feature. Herein, we aim to provide a comprehensive review on the internal motions of complex macromolecular systems of non-linear architecture. The review is organized as follows: firstly, we will briefly discuss the theoretical and experimental background of internal motions of linear chains; secondly, we will introduce the research progress of internal motions of typical complex macromolecular systems, including hyperbranched polymers, microgels/macrogels, graft polymers and polymeric assemblies/clusters; in the end, a few unresolved questions are enumerated for future studies. We hope this review can afford useful information for understanding the intrachain dynamics of complex macromolecular systems and stimulate the development of universal theory for these systems. Graphical abstract: Image 1